Corporate Social Responsibility, Investor Protection, and Earnings Management: Some International Evidence - Chih, Hsiang-Lin (Journal of business ethics, 2008)
To many, recent allegations of accounting fraud (or earnings management; EM) at Enron, coupled with similar ones at many other corporations, are a strong indication of a serious decay in business ethics. In academics, this raises the concern between EM and corporate social responsibility (CSR). Since it has neither been documented, nor globally tested whether CSR mitigates or increases the extent of EM, three kinds of EM are studied: earnings smoothing, earnings aggressiveness, and earnings losses and decreases avoidance. The extents to which financial characteristics and institutional variables have an impact on the extent to which companies conduct EM are also tested. Our study investigates whether the CSR-related features of 1,653 corporations in 46 countries had a positive or negative effect on the quality of their publicly released financial information during the 1993–2002 period. There is no question that with a greater commitment to CSR, the extent of earnings smoothing is mitigated, that of earnings losses and decreases avoidance is reduced, but the extent of earnings aggressiveness is increased.